Effects of brain renin- angiotensin system inhibition in ISIAH rats with inherited stress-induced arterial hypertension - L. O. Klimov; M. A. Ryazanova; L. A. Fedoseeva; A. L. Markel (Вавиловский журнал генетики и селекции)
The renin-angiotensin system (RAS) is one of the main systems regulating arterial pressure and water-salt homeostasis of the body and is involved in the pathogenesis of cardiovascular diseases. Angiotensin peptides – products of enzymatic hydrolysis of angiotensinogen – can be synthesized not only in the blood stream, but also in tissues, including various regions  of the brain. Studies of local tissue RAS in the context of arterial hypertension have been conducted for a long time. It has been shown that a steady arterial pressure increase is often associated with changes in the functioning of the central (brain) RAS in various animal models of hypertensive disease and in humans. Nevertheless, it is still not completely clear whether these changes alone are sufficient for the formation of hypertensive status, and whether the components of the central RAS can be used as targets for the treatment of hypertensive disease. Eﬀects of prolonged inhibition of the brain RAS on blood pressure and expression of RAS genes in brain and kidney tissues in ISIAH (inherited stress-induced arterial hypertension) rats were studied. Inhibition was performed using widely used pharmacological agents, losartan and benazepril. Osmotic minipumps were used to deliver drugs to the lateral ventricle of the brain. It was shown that prolonged inhibition of the central RAS, AT1 receptors in particular, can lead to a decrease in blood pressure and signiﬁcant changes in the level of expression of brain RAS genes in ISIAH rats. The mRNA level of RAS genes in the kidney does not signiﬁcantly change due to this inhibition. Thus, the participation of the central RAS in the pathogenesis and maintenance of hypertensive status during stress induced form of hypertensive disease in ISIAH rats was conﬁrmed.